Selective and Simultaneous Determination of Dihydroxybenzene Isomers Based on Green Synthesized Gold Nanoparticles Decorated Reduced Graphene Oxide. Issue 5 (22nd January 2015) - Palanisamy, Selvakumar; Karuppiah, Chelladurai; Chen, Shen‐Ming; Muthupandi, K.; Emmanuel, R.; Prakash, P.; Elshikh, Mohamed S.; Ajmal Ali, M.; Al‐Hemaid, Fahad M. A.
Abstract In the present study, we report the simultaneous electrochemical determination of hydroquinone (HQ), catechol (CC) and resorcinol (RC) at gold nanoparticles (Au‐NPs) decorated reduced graphene oxide (RGO) modified electrode. An enhanced and well defined peak current response with a better peak separation of HQ, CC and RC is observed at RGO/Au‐NPs composite than that of RGO and Au‐NPs modified electrodes. The fabricated modified electrode shows a wide linear response in the concentration range of 3–90 µM, 3–300 µM and 15–150 µM for HQ, CC and RC, respectively. The detection limit of HQ, CC and RC is found as 0.15 µM, 0.12 µM and 0.78 µM, respectively.